MINAT INVESTASI PEKERJA MIGRAN INDONESIA DALAM MENINGKATKAN KETAHANAN EKONOMI KELUARGA DI LAMPUNG TIMUR - Enny Puji Lestari; Nyimas Lidya Putri Pertiwi; Agus Alimuddin; Danil Asbihani (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2023)
This study is to determine the investment interest of former migrant workers in improving family resilience in East Lampung and the strategies carried out by former migrant workers in increasing family economic resilience in East Lampung. Data collection by observation and interviews, data analysis techniques by collecting data on migrant worker participants in East Lampung who returned from abroad in the last 5 years at the East Lampung Manpower Office, besides that the author also collected data on former migrant workers, then reduced data and presented data. East Lampung is the 5th largest migrant worker working abroad, the investment interest of former migrant workers in improving family resilience in East Lampung is quite high, income from work is used for positive needs. In addition, factors that influence the investment interest of former migrant workers are due to interest, desire and belief. The strategy in increasing family resilience carried out by former migrant workers in East Lampung utilizes the results of work to be managed by families properly and remain productive.